Composite material and preparation method thereof, solid-state battery and electrical equipment
By using graphite and solid electrolyte to coat composite materials in solid state batteries, the problem of poor contact between the negative electrode material and the solid electrolyte is solved, and the electrochemical performance and preparation efficiency of the battery are significantly improved.
Patent Information
- Application Number
- CN202210866469.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-22
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2042-07-22
AI Technical Summary
In existing solid-state batteries, the negative electrode material has poor contact with the solid electrolyte, resulting in poor electrochemical performance of the battery.
Composite materials are used, with graphite as the core and solid electrolyte as the cladding material. Through dispersion and heating treatment, the solid electrolyte is ensured to fully coat the graphite, thereby improving contactability.
It improves the first-effect and cycling performance of solid-state batteries, reduces the interface resistance, simplifies the negative electrode preparation process, and avoids the use of toxic solvents.
Smart Images

Figure BDA0003759393500000111 
Figure BDA0003759393500000121 
Figure BDA0003759393500000122
Abstract
Description
Technical Field
[0001] The present application belongs to the field of secondary batteries and relates to a composite material and a preparation method thereof, a solid-state battery and electrical equipment. Background Art
[0002] Solid-state batteries have been widely studied by enterprises and universities due to their excellent safety performance and high energy density. Solid electrolytes are used in solid-state batteries to replace the volatile and flammable liquid electrolytes and diaphragms in traditional lithium-ion batteries. Compared with liquid electrolytes, solid electrolytes have the advantages of no flammability, no corrosion, and high mechanical strength. They avoid the dangers of electrolyte leakage and electrode short circuit in traditional lithium-ion batteries, and reduce the sensitivity of battery packs to temperature. Due to the high mechanical strength of solid electrolytes, they can effectively prevent the growth of lithium dendrites and have extremely high safety during use. At present, the negative electrode materials used in all-solid-state lithium-ion batteries are mainly lithium metal, lithium indium metal, silicon, and graphite. Among them, lithium metal and lithium indium metal face the rapid growth of lithium dendrites during use, and lithium metal or lithium indium metal reacts with most sulfide solid electrolytes, causing the interface resistance to increase continuously, seriously affecting the battery's cycle performance. Lithium metal or lithium indium metal needs to be processed into metal foil with a thickness of micrometers for all-solid-state batteries, and the complex preparation process makes it extremely expensive. During use, the silicon negative electrode faces the problem of huge volume expansion due to lithium insertion, which leads to pulverization of active materials and seriously affects its cycle performance. Graphite, as a commonly used negative electrode material for lithium-ion batteries, has the advantages of stable structure during lithium insertion / de-lithiation and good cycle stability. However, in solid-state batteries, if graphite is simply mixed with solid electrolyte, it cannot ensure that the solid electrolyte is in full contact with graphite, and thus it cannot ensure that the solid electrolyte is well infiltrated into the graphite material, which greatly affects the charge and discharge capacity of the negative electrode active material and affects the cycle stability of the battery.
[0003] Based on this, there is an urgent need to provide a composite material that can fully contact with the solid electrolyte. Summary of the invention
[0004] The purpose of this application is to provide a composite material and a preparation method thereof, a solid-state battery and an electrical device, aiming to solve the technical problem that the contact between the negative electrode material and the solid electrolyte in the existing solid-state battery is poor, resulting in poor electrochemical performance of the battery.
[0005] To achieve the above-mentioned object, the present application provides a composite material in a first aspect, comprising a core and a coating layer arranged on the surface of the core;
[0006] The inner core comprises graphite;
[0007] The material of the coating layer includes a solid electrolyte.
[0008] In the composite material, the particle size Dv50 of the graphite may be 2 to 8 μm.
[0009] In the present application, the particle size Dv50 of the graphite may specifically include 5 μm, 8 μm, 10 μm or 5 to 8 μm.
[0010] The coating layer may have a thickness of 50 to 150 nm, and specifically may include 50 nm, 125 nm, 130 nm, 150 nm, 50 to 125 nm, 50 to 130 nm, 125 to 130 nm, or 125 to 150 nm.
[0011] In one embodiment, the solid electrolyte includes one or more of a sulfide solid electrolyte, a halide solid electrolyte, and a metal oxide solid electrolyte.
[0012] In the above composite materials, the sulfide solid electrolyte includes glassy xLi2S·(100-x)P2S5, Li-PS glass ceramics, argyrodite-type Li6PS5X, Li 11-c M 2-c P 1+c S 12 , wherein 20≤x≤80, X is selected from at least one of Cl, Br and I, M is selected from at least one of Ge, Sn and Si, and c is 0-5.
[0013] In the above composite material, the sulfide solid electrolyte can be selected from Li6PS5Cl, Li3PS4, 70Li2S·30P2S5, Li 11 Si2P1S 12 and Li 10 GeP2S 12 At least one of .
[0014] In the present application, the Li6PS5Cl is prepared according to the following method: the raw materials Li2S, P2S5 and LiCl are ball-milled at 500-600 rpm / min according to the molar ratio, and then sintered at a high temperature of 500-600°C to synthesize Li6PS5Cl;
[0015] The Li3PS4 is prepared according to the following method: the raw materials Li2S, P2S5 and LiCl are ball-milled at 500-600 rpm / min according to the molar ratio, and then sintered at a high temperature of 300-450° C. to synthesize Li3PS4;
[0016] The 70Li2S·30P2S5 is prepared as follows: the raw materials Li2S and P2S5 are ball-milled at 500-600 rpm according to the molar ratio, and then sintered at a high temperature of 200-350° C. to synthesize 70Li2S·30P2S5;
[0017] Preparation of the Li 11 Si2P1S 12 According to the following method: the raw materials Li2S, P2S5, and SiS2 are ball-milled at 500-600 rpm according to the molar ratio, and then sintered at a high temperature of 400-600°C to synthesize the Li 11 Si2P1S 12 ;
[0018] Preparation of the Li 10 GeP2S 12 According to the following method: the raw materials Li2S, P2S5, GeS2 are ball-milled at 500-600rpm according to the molar ratio, and then sintered at a high temperature of 400-600°C to synthesize the Li 11 Si2P1S 12 .
[0019] In the above composite material, the graphite is in at least one of a granular, flake, sheet and block shape;
[0020] The solid electrolyte exists on the graphite surface in the form of surface coating and / or point coating.
[0021] In the composite material, based on the mass of the composite material, the content of the graphite may be 85% to 95%, and the content of the solid electrolyte may be 5% to 15%.
[0022] The second aspect of the present application provides a method for preparing the above-mentioned composite material, comprising the following steps: adding the solid electrolyte and graphite into a first solvent, dispersing and heating to obtain the composite material.
[0023] In the above-mentioned preparation method, the step of adding the solid electrolyte and graphite into the first solvent, dispersing and drying to obtain the composite material comprises:
[0024] Adding the solid electrolyte into a first solvent to obtain a first mixed solution;
[0025] adding the graphite into the first mixed solution and performing a dispersion treatment to obtain a second mixed solution;
[0026] The second mixed solution is heated at a first preset temperature to evaporate the first solvent to obtain the composite material.
[0027] In the above preparation method, the first solvent includes anhydrous ethanol and / or N-methylpyrrolidone, and the first preset temperature is 70-85°C.
[0028] In the present application, 0.1 gram of the solid electrolyte is mixed with 1-20 mL of the first solvent.
[0029] In the present application, the treatment adopts ultrasound.
[0030] A third aspect of the present application provides a negative electrode, which includes a binder, a conductive agent, a first sulfide solid electrolyte and the above-mentioned composite material.
[0031] In the present application, the negative electrode comprises the following components in percentage by mass, with the total amount of the negative electrode being 100%:
[0032] Composite materials account for 85% to 95%;
[0033] Binder accounts for 0.5% to 2%;
[0034] Conductive agent accounts for 3% to 10%;
[0035] The remainder is the first solid electrolyte.
[0036] In the above-mentioned negative electrode, the binder is selected from at least one of PTFE, SBR, NBR and PVDF, preferably PTFE;
[0037] The conductive agent is selected from at least one of SuperP, acetylene black, Ketjen black, carbon black, carbon nanotubes, graphene and carbon fiber.
[0038] In the present application, the negative electrode is specifically made of the following components in percentage by weight, with the total amount being 100%:
[0039] The composite material 90%;
[0040] The binder 1%;
[0041] Conductive agent 4%;
[0042] Solid electrolyte 5%.
[0043] In the present application, the thickness of the negative electrode may be 100-300 μm, specifically 100 μm, 150 μm, 200 μm, 300 μm, 100-150 μm, 150-200 μm, 200-300 μm, 100-200 μm or 150-300 μm.
[0044] The fourth aspect of the present application provides a method for preparing the above-mentioned negative electrode, comprising the following steps: 1) ball-milling the composite material, the binder, the conductive agent, and the first solid electrolyte according to a proportion to obtain a ball-milled mixed raw material;
[0045] 2) Roll-pressing the ball-milled mixed raw material to obtain the negative electrode.
[0046] In the above preparation method, the ball milling speed in step 1) can be 200-350 rpm / min, and the ball milling time can be 30-60 min;
[0047] The ball milling is carried out in a zirconia ball mill jar using zirconia balls with a diameter of 2-10 mm;
[0048] In step 2), the rolling is performed on a roller press;
[0049] The conditions of the rolling are as follows:
[0050] The spacing between the upper roller and the lower roller of the roller press may be 100 μm to 300 μm;
[0051] The roller speed can be 1-3m / min.
[0052] A fifth aspect of the present application provides a solid-state battery, comprising a positive electrode, a first solid electrolyte layer and the above-mentioned negative electrode.
[0053] A sixth aspect of the present application provides an electrical device, which includes the above-mentioned solid-state battery, wherein the solid-state battery serves as a power supply for the electrical device.
[0054] This application has the following beneficial effects:
[0055] 1. The composite material of the present application is used to prepare the negative electrode. Since the solid electrolyte is coated on the surface of graphite, it is conducive to the full contact between the solid electrolyte and the graphite, which promotes the use of the capacity of the negative electrode active material (graphite), thereby improving the initial efficiency of the battery and improving the battery cycle performance; secondly, the flexible graphite negative electrode is in more effective contact with the solid electrolyte layer, which reduces the interface resistance and promotes the lithium ion transmission at the interface.
[0056] 2. The method of preparing the negative electrode using composite materials utilizes the fact that the binder is easy to fiberize and form a film under the action of high-speed shear force. The raw materials are mixed and rolled to form a self-supporting negative electrode with a thickness of micrometer level. The preparation method is simple, and no toxic solvents are needed to form the negative electrode, thus avoiding the steps of drying the toxic solvents and post-treatment of the solvents, greatly reducing the steps of negative electrode preparation, and avoiding the harm of toxic solvents to the environment and humans during the negative electrode preparation process.
[0057] 3. The negative electrode structure is conducive to the transmission of ions and electrons, and there is no need to use copper foil as a current collector. When used as the negative electrode of a solid-state battery, it can reduce the overall weight of the solid-state battery and save costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 This is a schematic diagram of the structure of the composite material particles of Example 1 of the present application, wherein A is graphite and B is a composite material having solid electrolyte coated graphite.
[0059] Figure 2 This is a schematic diagram of the solid-state battery of Example 1 of the present application.
[0060] Figure 2 The tags are as follows:
[0061] 1 negative electrode; 2 solid electrolyte layer; 3 positive electrode. DETAILED DESCRIPTION
[0062] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0063] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0064] The present application first provides a composite material, comprising a core and a coating layer arranged on the surface of the core;
[0065] The inner core comprises graphite;
[0066] The material of the coating layer includes a solid electrolyte.
[0067] The present application utilizes a solid electrolyte to coat graphite, thereby improving the contact performance between the solid electrolyte and the graphite surface, effectively "infiltrating" the solid electrolyte into the graphite, and thus facilitating the utilization of the capacity of the active material.
[0068] Furthermore, in order to improve the wettability of the electrolyte in the electrode and avoid insufficient contact due to the graphite particle size being too large or too small, thereby affecting the lithium ion transmission at the interface, the particle size Dv50 of the graphite may include 2 to 8 μm;
[0069] The thickness of the coating layer may be 50 to 150 nm, and specifically may be 50 nm, 125 nm, 130 nm, or 150 nm.
[0070] Solid electrolytes include one or more of sulfide solid electrolytes, polymer solid electrolytes, halide solid electrolytes, and metal oxide solid electrolytes. Among them, halide solid electrolytes include Li3InCl6, Li3YCl6, Li3TbCl6, and Li3ErCl6; metal oxide solid electrolytes include LiAlO2, Li2ZrO3, Li4Ti5O 12 Since sulfide solid electrolyte has excellent electrical conductivity, the present application uses sulfide solid electrolyte as the coating material.
[0071] Furthermore, in order to promote the transmission of electrons and eliminate the need to use copper foil as a current collector to reduce the weight of the negative electrode to prepare a solid-state battery and save costs, the sulfide solid electrolyte may include Li6PS5Cl, Li3PS4, 70Li2S·30P2S5, Li10 GeP2S 12 , Li 11 Si2P1S 12 .
[0072] In the following examples, the Li6PS5Cl is prepared according to the following method: the raw materials Li2S, P2S5 and LiCl are ball-milled at 500-600 rpm / min according to the molar ratio, and then sintered at a high temperature of 500-600°C to synthesize Li6PS5Cl;
[0073] The Li3PS4 is prepared according to the following method: the raw materials Li2S, P2S5 and LiCl are ball-milled at 500-600 rpm / min according to the molar ratio, and then sintered at a high temperature of 300-450° C. to synthesize Li3PS4;
[0074] The 70Li2S·30P2S5 is prepared as follows: the raw materials Li2S and P2S5 are ball-milled at 500-600 rpm / min according to a molar ratio of 7:3, and then sintered at a high temperature of 200-350° C. to synthesize 70Li2S·30P2S5;
[0075] Preparation of the Li 11 Si2P1S 12 According to the following method: the raw materials Li2S, P2S5, and SiS2 are ball-milled at 500rp-600m / min according to the molar ratio, and then sintered at a high temperature of 400-600°C to synthesize the Li 11 Si2P1S 12 ;
[0076] Preparation of the Li 10 GeP2S 12 According to the following method: the raw materials Li2S, P2S5, GeS2 are ball-milled at 500-600rpm / min according to the molar ratio, and then sintered at a high temperature of 400-600°C to synthesize the Li 11 Si2P1S 12 .
[0077] Furthermore, in order to make the flexible negative electrode more effectively contact the solid electrolyte layer, the following graphite shapes and coating forms are preferred, wherein the graphite shape is at least one of granular, phosphorus flake, sheet and block;
[0078] The solid electrolyte exists on the graphite surface in the form of surface coating and / or point coating.
[0079] In the composite material, the mass percentage of the graphite coated with the solid electrolyte is 85% to 95%, and the mass percentage of the sulfide solid electrolyte is 5 to 15%.
[0080] In order to prepare the above composite material, the following steps are included:
[0081] Adding the solid electrolyte into anhydrous ethanol to obtain a first mixed solution;
[0082] adding the graphite into the first mixed solution and performing ultrasonic dispersion treatment to obtain a second mixed solution;
[0083] The second mixed solution is heated at 70-85° C., and the anhydrous ethanol is evaporated to obtain the composite material.
[0084] Every 0.1 gram of the sulfide solid electrolyte is mixed with every 1 to 20 ml of the anhydrous ethanol.
[0085] The present application also provides a negative electrode, which includes a binder, a conductive agent, a first solid electrolyte and the composite material mentioned above. In the present application, the type of the first solid electrolyte is the same as the type of the solid electrolyte.
[0086] The negative electrode is specifically made of the following components in percentage by mass, with the total mass of the negative electrode being 100%:
[0087] Composite materials account for 85% to 95%;
[0088] Binder accounts for 0.5% to 2%;
[0089] The conductive agent accounts for 3% to 10%; the first solid electrolyte accounts for 1% to 8%.
[0090] The present application also provides a method for preparing the above-mentioned negative electrode, comprising the following steps: 1) ball-milling the composite material, the binder, the conductive agent, and the first solid electrolyte according to a proportion to obtain a ball-milled mixed raw material;
[0091] 2) Roll-pressing the ball-milled mixed raw material to obtain the negative electrode.
[0092] In the above preparation method, the ball milling speed in step 1) can be 200-350 rpm / min, and the ball milling time can be 30-60 min;
[0093] In order to provide sufficient shear force to fiberize the binder, the ball milling is performed in a zirconia ball mill using zirconia balls with a diameter of 2 to 10 mm;
[0094] In step 2), in order to obtain the desired thickness of the negative electrode, the distance between the upper roller and the lower roller of the roller press is controlled, and the distance between the upper roller and the lower roller of the roller press can be 100 μm to 300 μm;
[0095] In order to make the prepared negative electrode support performance better, the following rolling parameters are optimized, and the roller speed can be 1-3m / min.
[0096] The present application also provides a solid-state battery, comprising a positive electrode, a solid electrolyte layer and the above-mentioned negative electrode, wherein the solid electrolyte layer comprises a second solid electrolyte, and the second solid electrolyte is of the same type as the first solid electrolyte and the solid electrolyte in the coating layer.
[0097] In another embodiment, the solid electrolyte in the coating layer, the first solid electrolyte in the negative electrode, and the second solid electrolyte in the solid electrolyte layer have different particle Dv50 and different specific surface areas, wherein the particle Dv50 is from large to small, which is the second solid electrolyte in the solid electrolyte layer, the solid electrolyte in the coating layer, and the first solid electrolyte in the negative electrode. The particles of the first solid electrolyte in the negative electrode are nanometer-sized, with a Dv50 of 5 to 35 nm and a specific surface area of 200 to 350 m 2 / g; the particles of the second solid electrolyte have a Dv50 of 8 to 15 μm and a specific surface area of 12 to 28 m 2 / g; the particles of the solid electrolyte in the coating layer are nanometer-sized, with a Dv50 of 50 to 150 nm and a specific surface area of 80 to 130 m 2 / g. The first solid electrolyte in the negative electrode has the smallest particle Dv50, which can be effectively filled between the composite materials to improve the lithium ion conduction and electronic conduction performance of the negative electrode. The second solid electrolyte in the solid electrolyte layer is a place for lithium ion transmission. If the Dv50 of the second solid electrolyte is too large, the lithium ion diffusion path will be too long, and if its Dv50 is too small, it will easily cause side reactions, which is not conducive to the performance of the battery.
[0098] The present application also provides an electrical device, which includes the above-mentioned solid-state battery, wherein the solid-state battery serves as a power supply for the electrical device.
[0099] The present application is described in detail below in conjunction with embodiments and drawings.
[0100] Example 1
[0101] 1. Preparation of composite materials:
[0102] (1) dispersing 0.415 g of Li6PS5Cl (referred to as LPSC) in 50 mL of anhydrous ethanol to form a first mixed solution;
[0103] (2) dispersing 4.585 g of graphite with a Dv50 of 4 μm in the first mixed solution and performing ultrasonic dispersion treatment for 1 h to form a second mixed solution;
[0104] (3) The second mixed solution was vacuum dried at 80° C., and the anhydrous ethanol was evaporated to obtain a composite material of Li6PS5Cl coated graphite (LPSC@Gr), wherein the graphite content in the composite material was 91.7%, the Li6PS5Cl content was 8.3%, and the thickness of the coating layer was 120 nm.
[0105] 2. Preparation of negative electrode:
[0106] (1) The composite material, binder (PTFE), conductive agent (graphene), and LPSC prepared above were weighed in a ratio of 90:1:4:5, totaling 5 g, and the weighed raw materials were placed in a zirconia ball mill, and then 50 g of zirconia balls with a diameter of 10 mm were added for ball milling, wherein the ball milling speed was 200 rpm / min and the ball milling time was 30 min.
[0107] (2) The ball-milled raw material was rolled using a roller press, the spacing between the upper roller and the lower roller was adjusted to 100 μm, the roller speed was adjusted to 1 m / min, and after cutting and cold pressing, a negative electrode with a thickness of 100 μm was obtained.
[0108] 3. Preparation of solid-state batteries
[0109] (1) Preparation of solid electrolyte sheets
[0110] The sulfide solid electrolyte (LPSC) was placed in a mold and a solid electrolyte sheet with a thickness of 100 μm and a diameter of 10 mm was prepared by applying a pressure of 10 MPa.
[0111] (2) Preparation of positive electrode
[0112] In a glove box, the positive electrode material LNO@NCM622 and the sulfide solid electrolyte (LPSC) were weighed in a mass ratio of 70:30, and ground and mixed evenly. LNO@NCM622 refers to LiNbO3 coated with LiNi2Co2Mn2O2, and the coating amount of LiNbO3 in the positive electrode material is 0.5% to 1%. 20 mg of the mixed material was weighed and placed in a solid-state battery mold with a diameter of 10 mm, and a pressure of 10 MPa was applied to obtain a positive electrode press, and a carbon-coated aluminum foil disc with a diameter of 10 mm was placed on the side as a current collector to obtain a positive electrode.
[0113] (3) Preparation of solid-state batteries
[0114] The above-mentioned positive electrode 3, solid electrolyte sheet (i.e., sulfide solid electrolyte layer) 2, and negative electrode 1 are assembled into a solid-state battery (the structure of the solid-state battery is shown in FIG. 1 ). Figure 2 ).
[0115] Example 2
[0116] The same as Example 1 of the present application, except that, during the preparation of the composite material, 0.325 g of Li6PS5Cl and 4.675 g of graphite were added, and the graphite content of the prepared composite material was 93.5%, the Li6PS5Cl content was 6.5%, and the thickness of the coating layer was 85 nm.
[0117] Embodiment 3,
[0118] The same as Example 1 of the present application, except that, during the preparation of the composite material, 0.25 g of Li6PS5Cl and 4.75 g of graphite were added, and the graphite content of the prepared composite material was 95%, the Li6PS5Cl content was 5%, and the thickness of the coating layer was 50 nm.
[0119] Embodiment 4,
[0120] The same as Example 1 of the present application, except that, during the preparation of the composite material, 0.375 g of Li6PS5Cl and 4.625 g of graphite were added, and the graphite content of the prepared composite material was 92.5%, the Li6PS5Cl content was 7.5%, and the thickness of the coating layer was 100 nm.
[0121] Embodiment 5,
[0122] The same as Example 1 of the present application, except that, during the preparation of the composite material, 0.75 g of Li6PS5Cl and 4.25 g of graphite were added, and the graphite content of the prepared composite material was 85%, the Li6PS5Cl content was 15%, and the thickness of the coating layer was 150 nm.
[0123] Example 6
[0124] The same as Example 1 of the present application, except that during the preparation of the composite material, the graphite Dv50 is 2 μm.
[0125] Example 7
[0126] The same as Example 1 of the present application, except that during the preparation of the composite material, the graphite Dv50 is 5 μm.
[0127] Example 8
[0128] The same as Example 1 of the present application, except that during the preparation of the composite material, the graphite Dv50 is 6 μm.
[0129] Example 9
[0130] The same as Example 1 of the present application, except that during the preparation of the composite material, the graphite Dv50 is 8 μm.
[0131] Example 10
[0132] The same as Example 1 of the present application, except that during the preparation of the composite material, the graphite Dv50 is 1 μm.
[0133] Embodiment 11
[0134] The same as Example 1 of the present application, except that during the preparation of the composite material, the graphite Dv50 is 10 μm.
[0135] Example 12
[0136] The method is the same as Example 1 of the present application, except that, during the preparation of the negative electrode, the spacing between the upper roller and the lower roller is adjusted to 125 μm, so as to obtain a negative electrode with a thickness of 125 μm.
[0137] Embodiment 13
[0138] The method is the same as Example 1 of the present application, except that, during the preparation of the negative electrode, the spacing between the upper roller and the lower roller is adjusted to 200 μm, so as to obtain a negative electrode with a thickness of 200 μm.
[0139] Embodiment 14
[0140] The method is the same as Example 1 of the present application, except that, during the preparation of the negative electrode, the spacing between the upper roller and the lower roller is adjusted to 300 μm, so as to obtain a negative electrode with a thickness of 300 μm.
[0141] Embodiment 15
[0142] The method is the same as Example 1 of the present application, except that, during the preparation of the negative electrode, the spacing between the upper roller and the lower roller is adjusted to 75 μm, so as to obtain a negative electrode with a thickness of 75 μm.
[0143] Example 16
[0144] The method is the same as Example 1 of the present application, except that, during the preparation of the negative electrode, the spacing between the upper roller and the lower roller is adjusted to 350 μm, so as to obtain a negative electrode with a thickness of 350 μm.
[0145] Application Example 17
[0146] The method is the same as Example 5 of the present application, except that, in the preparation of the composite material: the sulfide solid electrolyte is Li3PS4 (LPS for short), and Li3PS4-coated graphite (LPS@Gr) is obtained.
[0147] The steps for preparing the negative electrode are:
[0148] Step (2) The spacing between the upper roller and the lower roller is adjusted to 200 μm, and the roller speed is adjusted to 1 m / min to obtain a negative electrode with a thickness of 200 μm.
[0149] In the preparation steps of solid-state batteries:
[0150] The difference is that the sulfide solid electrolyte is LPS.
[0151] Embodiment 18
[0152] The same as Example 1 of the present application, except that in the preparation steps of the composite material:
[0153] 0.5g sulfide solid electrolyte Li 10 GeP2S 12 (LGPS for short); 4.5g Dv50 is 10μm graphite, obtain Li 10 GeP2S 12 The coated graphite (LGPS@Gr) (the mass percentage content of graphite is 90%, and the mass percentage content of LGPS is 10%), wherein the thickness of the LGPS layer is 125 nm.
[0154] The steps for preparing the negative electrode are:
[0155] Step (2) The spacing between the upper roller and the lower roller is adjusted to 150 μm to obtain a negative electrode with a thickness of 150 μm.
[0156] The preparation steps of solid-state batteries:
[0157] The difference is that the sulfide solid electrolyte is LGPS.
[0158] Embodiment 19
[0159] The same as Example 1 of the present application, except that the sulfide solid electrolyte is 70Li2S·30P2S5.
[0160] Embodiment 20
[0161] The same as Example 1 of the present application, except that the sulfide solid electrolyte is Li 11 Si2P1S 12 .
[0162] Embodiment 21
[0163] 1. Preparation steps of composite materials:
[0164] (1) dispersing 0.75 g of sulfide solid electrolyte Li6PS5Cl in 45 mL of N-methylpyrrolidone (NMP) to form a first mixed solution;
[0165] (2) dispersing 4.25 g of graphite with a Dv50 of 5 μm in solution A and ultrasonically treating for 1 h to form a second mixed solution;
[0166] (3) The second mixed solution was vacuum dried at 80° C. to obtain Li6PS5Cl-coated graphite (LPSC@Gr) (the graphite content was 85% and the Li6PS5Cl content was 15%), wherein the thickness of the LPSC layer was 150 nm.
[0167] 2. Preparation steps of negative electrode:
[0168] The method is the same as Example 1 of the present application, except that 40 g of zirconia balls with a diameter of 10 mm are added for ball milling in step (1), wherein the ball milling speed is 200 rpm / min and the ball milling time is 30 min.
[0169] Step (2) The spacing between the upper roller and the lower roller is adjusted to 300 μm, and the roller speed is adjusted to 1 m / min to obtain a negative electrode with a thickness of 300 μm.
[0170] Embodiment 22
[0171] Same as Example 1 of the present application, except that:
[0172] 1. During the preparation of the composite material, 0.6 g of sulfide solid electrolyte Li6PS5Cl and 4.4 g of graphite with a Dv50 of 10 μm were used to obtain Li6PS5Cl-coated graphite (LPSC@Gr), in which the thickness of the LPSC layer was 130 nm.
[0173] 2. Preparation of negative electrode:
[0174] (1) Add 40 g of zirconia balls with a diameter of 10 mm for ball milling.
[0175] (2) The gap between the upper roller and the lower roller was adjusted to 150 μm, and the roller speed was adjusted to 1 m / min to obtain a negative electrode with a thickness of 150 μm.
[0176] Embodiment 23
[0177] 1. Preparation of composite materials: After LiCl, InCl3 and graphite are evenly dispersed in water, the water is evaporated by heating and stirring at 60°C to obtain a composite material of Li3InCl6 coated graphite. The graphite Dv50 of the composite material is 4μm, the graphite content accounts for 91.7%, the Li3InCl6 content accounts for 8.3%, and the thickness of the coating layer is 120nm.
[0178] 2. The preparation of the negative electrode is the same as that in Example 1.
[0179] 3. Preparation of solid-state battery: Same as in Example 1, except that the solid electrolyte is Li3InCl6.
[0180] Embodiment 24
[0181] 1. Preparation of negative electrode materials: Al2O3 and Li2CO3 with a mass ratio of 1:2 were evenly mixed by ball milling, and then calcined at 800°C for 10 hours in a vacuum tube furnace. LiAlO2 was obtained after cooling. LiAlO2 and graphite with a mass ratio of 1:9 were evenly dispersed in anhydrous ethanol, and the anhydrous ethanol was evaporated to obtain a negative electrode material precursor. The negative electrode material precursor was sintered at 400°C in a vacuum tube furnace to obtain a negative electrode material of LiAlO2 coated graphite. The graphite Dv50 of the composite material is 4μm, the graphite content accounts for 91.7%, the LiAlO2 content accounts for 8.3%, and the thickness of the coating layer is 120nm.
[0182] 2. The preparation of the negative electrode is the same as that in Example 1.
[0183] 3. Preparation of solid-state battery: Same as Example 1, except that the solid electrolyte is LiAlO2.
[0184] Comparative Example 1
[0185] Different from Example 1, during the preparation of the negative electrode material, 0.415 g of Li6PS5Cl and 4.585 g of graphite were replaced with 5 g of graphite to prepare a graphite negative electrode material without a sulfide solid electrolyte coating layer.
[0186] The relevant parameters of the composite materials and negative electrodes prepared in Examples 1-24 and Comparative Example 1 are recorded in Table 1, and the prepared solid-state battery is subjected to full battery performance test, and the test method is: the solid-state battery is subjected to rate charge and rate discharge using a Xinwei test cabinet. The battery test rate is 0.1C, the operating voltage range is 2.75-4.3V, and the cycle is 100 cycles.
[0187] The above solid-state battery test data are summarized to obtain Table 2.
[0188] Table 1
[0189]
[0190]
[0191] Table 2 Performance test results of solid-state batteries
[0192]
[0193] By comparing the different parameters in Table 1 and the performance results of solid-state batteries in Table 2, we can see that:
[0194] 1. According to the test data of the above-mentioned embodiments 1-24 and comparative example 1, compared with the composite material coated with a solid electrolyte, the negative electrode material without solid electrolyte coating has a significantly reduced test performance of the solid-state battery, which is shown as the first effect of only 62.2%, and the 100-cycle cycle retention rate is only 71.3. The reason is that when there is no solid electrolyte coating, the negative electrode active material (graphite) in the solid-state battery cannot be fully contacted with the solid electrolyte, resulting in the inability to ensure that the solid electrolyte is well infiltrated into the graphite material, thereby greatly affecting the first effect of the negative electrode active material, and affecting the cycle stability of the solid-state battery. In the present application, since the solid electrolyte serves as a channel for lithium ion transmission, when the contact performance of the solid electrolyte and graphite is poor, the capacity of the graphite will be reduced, causing a decrease in the first effect, so the quality of the contact performance of the solid electrolyte and graphite can be reflected by the size of the first effect.
[0195] 2. The test data of the above examples 1-5 show that the percentage of solid electrolyte can affect the electrochemical performance of solid-state batteries. When the content of solid electrolyte is 6.5-8.3%, the first charge and discharge efficiency of solid-state batteries is between 84.2% and 85.5%, and the 100-cycle capacity retention rate is between 92.2% and 98.5%.
[0196] 3. Through the examination of the Dv50 data of different graphites in the above-mentioned Example 1 and Examples 6-11, it can be seen that by comparing Examples 1, 6-9 of the present application with Examples 10-11, the particle size Dv50 of the graphite in the composite material can be 2 to 8 μm, and the performance of the solid-state battery prepared therefrom is better than that prepared in Examples 10-11. It can be seen that too large or too small a graphite particle size leads to insufficient contact, thereby affecting the lithium ion transmission at the interface.
[0197] 4. It can be seen from the test data of Examples 1-22 and Examples 22-23 that the solid-state battery made of sulfide solid electrolyte has better electrochemical performance than the battery made of halide solid electrolyte and oxide solid electrolyte. The reason is that the electrical conductivity of the sulfide solid electrolyte is greater than that of the halide solid electrolyte and the oxide solid electrolyte.
Claims
1. A solid-state battery, characterized in that: The solid-state battery comprises a positive electrode, a solid electrolyte layer and a negative electrode, wherein the negative electrode comprises a binder, a conductive agent, a first solid electrolyte and a composite material; The composite material comprises a core and a coating layer arranged on the surface of the core; the core comprises graphite; the material of the coating layer comprises a solid electrolyte; The solid electrolyte in the coating layer, the first solid electrolyte in the negative electrode, and the second solid electrolyte in the solid electrolyte layer have different particle Dv50 and different specific surface areas, wherein the particle Dv50 is, from large to small, the second solid electrolyte in the solid electrolyte layer, the solid electrolyte in the coating layer, and the first solid electrolyte in the negative electrode; The particles of the first solid electrolyte in the negative electrode are nanometer-sized, with a Dv50 of 5-35 nm and a specific surface area of 200-350 m 2 / g; the particles of the second solid electrolyte have a Dv50 of 8 to 15 μm and a specific surface area of 12 to 28 m 2 / g; the particles of the solid electrolyte in the coating layer are nanometer-sized, with a Dv50 of 50~150nm and a specific surface area of 80~130m 2 / g; The particle size Dv50 of the graphite is 2-8 μm.
2. The solid-state battery according to claim 1, characterized in that: The thickness of the coating layer is 50-150 nm.
3. The solid-state battery according to claim 1, characterized in that: The solid electrolyte includes one or more of a sulfide solid electrolyte, a halide solid electrolyte, and a metal oxide solid electrolyte.
4. The solid-state battery according to claim 3, characterized in that: The sulfide solid electrolyte includes glassy xLi2S·(100-x)P2S5, Li-PS glass ceramics, argyrodite-type Li6PS5X, Li 11-c M 2-c P 1+c S 12 , Wherein, 20≤x≤80, X is selected from at least one of Cl, Br and I, M is selected from at least one of Ge, Sn and Si, and c is 0-5.
5. The solid-state battery according to claim 1 or 2, characterized in that: The graphite is in at least one of granular, flake, sheet and block shapes; The solid electrolyte exists on the graphite surface in the form of surface coating and / or point coating.
6. The solid-state battery according to claim 1 or 2, characterized in that: Based on the mass of the composite material, the content of the graphite is 85% to 95%, and the content of the solid electrolyte is 5% to 15%.
7. The solid-state battery according to claim 1 or 2, characterized in that: The method for preparing the composite material is characterized by comprising the following steps: The solid electrolyte and graphite are added into a first solvent, dispersed and heated to obtain the composite material.
8. The solid-state battery according to claim 7, characterized in that: The step of adding the solid electrolyte and graphite into the first solvent, dispersing and drying the solid electrolyte and graphite to obtain the composite material comprises: Adding the solid electrolyte into a first solvent to obtain a first mixed solution; adding the graphite into the first mixed solution and performing a dispersion treatment to obtain a second mixed solution; The second mixed solution is heated at a first preset temperature to evaporate the first solvent to obtain the composite material.
9. An electrical device, characterized in that: It comprises the solid-state battery according to any one of claims 1 to 8, wherein the solid-state battery serves as a power supply for the electrical device.
Citation Information
Patent Citations
Negative electrode material, preparation method of negative electrode material, negative electrode and full-solid-state lithium ion battery
CN107665994A
All-solid-state lithium ion battery and negative electrode mix
WO2020116324A1
Solid-state battery
WO2021246043A1